Morphology, molecular identification, and pathogenicity of Vibrio spp. on blood clam (Anadara granosa) in Yogyakarta, Indonesia tourism beach areas - ANNA ROOSIANA DEVI; Ari Susilowati; RATNA SETYANINGSIH (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Devi AR, Susilowati A, Setyaningsih R. 2019. Morphology, molecular identification, and pathogenicity of Vibrio spp. on blood clam (Anadara granosa) in Yogyakarta, Indonesia tourism beach areas. Biodiversitas 20: 2890-2896. Seafood is very popular among Indonesian people, especially in coastal areas. In Bantul Yogyakarta, blood clams have become one of tourist's favorite, either cooked or raw. Blood clams are filter feeders that cause the clams to be vulnerable to contamination of pathogenic bacteria that can cause foodborne disease, including Escherichia, Pseudomonas, and Vibrio. The 10-20% cases of foodborne disease transmitted through seafood caused by Vibrio spp. Three species of Vibrio can cause foodborne disease in humans, i.e., V. cholerae, V. parahaemolyticus, and V. vulnificus. The purpose of this study was to determine the character of Vibrio using morphological and molecular identification and pathogenicity on blood clam (Anadara granosa). Blood clams samples were collected from Depok, Goa Cemara, and Kwaru beaches in Bantul, Yogyakarta, Indonesia. Isolation of Vibrio spp. from blood clams was done using selective differential Thiosulfate Citrate bile salts sucrose (TCBS) culture medium. The morphological characters of the isolate colonies were determined based on the color, shape, texture, and size of the colony. Hemolysis test was also performed to evaluate the pathogenicity by using blood agar media. Molecular identification of Vibrio species was made using 16S rRNA sequence. Phylogenetic analysis was performed using Neighbor-Joining method in Mega X software. Samples for the analysis came from DNA sequences of this study and those from the GenBank database. Of the total 15 isolates obtained, four isolates showed positive ?-hemolysis, namely, isolate P2S2 -1bH, P3S1-1aH, P2S1-1aK and P2S2-1aK, and one isolate had positive ?-hemolysis (P3S2-1aK). Seven species of Vibrio were identified as V. algynolyticus, V. parahaemolyticus, V. diabolicus, V neocaledonicus, V. azureus, V. natrigens, and V. cholerae.